Nursing faculty's point of view regarding noncompliance with ethics in academic environments: a qualitative study - Mohsen Taghadosi; Sina Valiee; Mohammad Aghajani (BMC, 2021)
Abstract Background An academic environment is the first place that nursing students are introduced to ethics related to nursing and healthcare. In this study, we explored the nursing faculty members' point of view regarding noncompliance with these academic ethics. Methods This study was a qualitative descriptive study conducted in 2018. Faculty members at a nursing school were selected through purposeful sampling. Data was collected using semi-structured interviews. The interviews were digitally recorded and transcribed verbatim. Data collection and data analysis were conducted simultaneously. Data saturation was ensured with 11 interviews. The interview transcripts were analyzed using a qualitative content analysis method introduced by Elo and Kyngäs. Results The participants were six women and five men with 12.72 ± 6.64 years of experience as nursing instructors. After data analysis, seven categories were identified: discrimination, violence, misuse, out-of-date instruction and knowledge, conflicts of evaluation, hypocrisy, and disorganization. Conclusion The findings of this study indicated the existence of noncompliance regarding academic ethics. It is recommended that faculty members be informed about possible instances of ethical noncompliance in academia. There is a need to develop strategies to promote a faculty's compliance with academic ethics. Academic administrators need to emphasize the importance of ethics in academia and use further methods to enhance academic ethics.